2021
DOI: 10.1101/2021.12.14.472674
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Qualifying a human Liver-Chip for predictive toxicology: Performance assessment and economic implications

Abstract: Human organ-on-a-chip (Organ-Chip) technology has the potential to disrupt preclinical drug discovery and improve success in drug development pipelines as it can recapitulate organ-level pathophysiology and clinical responses. The Innovation and Quality (IQ) consortium, formed by multiple pharmaceutical and biotechnology companies, has published guidelines that define criteria for qualifying preclinical models, however, systematic and quantitative evaluation of the predictive value of Organ-Chips has not yet b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 70 publications
2
28
0
Order By: Relevance
“…However, donors 2 and 4 demonstrated approximately a 20% decline in cell number by Day 14 as observed through bright-field imaging (scoring performed according to supplementary figure S2, donor 4 in supplementary figure S3). Similar LSEC morphology was demonstrated by donor one in a liver organoid model [23] and by donor three in human coculture [25], [30] and quad-culture [24] Liver-Chips, respectively.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…However, donors 2 and 4 demonstrated approximately a 20% decline in cell number by Day 14 as observed through bright-field imaging (scoring performed according to supplementary figure S2, donor 4 in supplementary figure S3). Similar LSEC morphology was demonstrated by donor one in a liver organoid model [23] and by donor three in human coculture [25], [30] and quad-culture [24] Liver-Chips, respectively.…”
Section: Resultssupporting
confidence: 63%
“…However, donors 2 and 4 demonstrated approximately a 20% decline in cell number by Day 14 as observed through bright-field imaging (scoring performed according to supplementary figure S2, donor 4 in supplementary figure S3). Similar LSEC morphology was demonstrated by donor one in a liver organoid model [23] and by donor three in human coculture [25], [30] and quad-culture [24] Liver-Chips, respectively. SEM is the gold standard for visualizing the ultrastructure of cells and reveals that 2-20% of the LSEC surface is covered with fenestrae that are either individually scattered or arranged in a sieve-like pattern [32] with no basement membrane, and no cytoplasmic projections such as filopodia [33].…”
Section: Human Liver-chip Maintains the Morphology Of Lsecs For 14 Da...supporting
confidence: 72%
See 1 more Smart Citation
“…One of the beneficial potentials and future perspectives of microfluidic devices was reported by Ewart et al, who analyzed Liver-Chip for its ability to predict DILI [ 106 ]. This study reported 80% sensitivity of compound toxicities, which has a significant potential in drug development, especially preclinical stage.…”
Section: Challenges In Designing Liver Disease-on-chip Modelsmentioning
confidence: 99%
“…This study reported 80% sensitivity of compound toxicities, which has a significant potential in drug development, especially preclinical stage. Moreover, the economic value model in the pharmaceutical industry for increased precision of preclinical studies estimated approximately USD 3 billion in benefits for Liver-Chip studies and for the use of other organ-chips with the same sensitivity up to USD 24 billion in benefits [ 106 ].…”
Section: Challenges In Designing Liver Disease-on-chip Modelsmentioning
confidence: 99%